Mosaic as an Element of the Synthesis of Architecture and Monumental Art in the Architecture of Volgograd and Volzhsky: An Advanced Research - Serebryanaya, Valentine; Shevchuk, Irina (Novel Perspectives of Engineering Research Vol. 1, 2021)
The article examines all the existing and lost mosaics displayed on public and residential buildings in the territory of Volgograd and Volzhsky. The issues of typology and stylistics of mosaics are also examined. The classification of the features of mosaic compositions has been carried out. The author makes an attempt to summarize and scientifically comprehend the creative work of Volgograd monumental artists. The article is supported by archival and exterior photographs. Many city mosaics are lost or significantly damaged. Therefore, it is important to study and preserve monumental art and carry out urgent restoration work where necessary.